Embryoid induction and plantlet regeneration from leaf segments of sugarcane (Saccharum officinarum L.) - A. Elhassan, Anas; H. Hamad, Samira; A. Ali, Mohamed (المجلة الزراعية, 2021)
Sugarcane (Saccharum officinarum L.) is an economically important crop in Sudan for domestic consumption and export. It is the first and essential source for production of high purity sugar. Tissue culture techniques can be used for in vitro conservation of sugarcane (Taylor and Dukic, 1993) and mass propagation of elite cultivars of crop species. Moreover, it was used for production of pathogen-free planting material from infected mother plants. Variability induced in vitro can furnish a base for improvement of vegetatively propagated crops including sugarcane. Different tissue culture techniques were applied successfully to sugarcane propagation and plant regeneration through organogenesis of shoot meristem (Nadar and Heinz, 1977; Ho and Vasil, 1983a), cell suspension cultures (Ho and Vasil, 1983b, Aftab et al., 1996) and protoplast cultures ( Liu, 1994). Cell suspen - Sion cultures were also used for cytological, pathological (Peros and Lombard, 1992), biochemical and physiological investigations of sugarcane (Heinz et al., 1977).      This study was initiated, during 1998-2000, to investigate the effect of 2,4-D on induction of embryogenic callus from leaf explants of sugarcane and regeneration of somatic embryos on different concen-trations of Murashige and Skoog (1962) medium (MS).